Antibiotics prescribing patterns in medical wards of Yangon General Hospital, Myanmar - Khaing, Aye Thi; Win, Nang Hla Hla (IIUM Medical Journal Malaysia, 2016)
Introduction: Irrational and inappropriate prescribing of antimicrobial is common in hospitals and contributes to the development of antibiotic resistance in clinical practice. In Myanmar, there is insufficient information concerning antibiotics prescribing patterns in some hospitals. Therefore, the aim of this study was to determine the prescribing patterns of antibiotics in various infections. Methods: A descriptive cross-sectional study was carried out over a 3- month period in the medical wards of Yangon General Hospital. A total 1054 patients who were prescribed with antibiotics for post-admission day were selected. Relevant demographic data, discharge diagnosis, antibiotic prescribing patterns and outcomes of the patients were collected through pro-forma. Results: The result revealed that the antibiotics prescribing rate in Yangon General Hospital was 49%. Amongst the major indications included acute gastroenteritis (10%), chest infections (6.8%), skin and soft tissue infections (6.5%), pneumonia (6.1%) and spontaneous bacterial peritonitis (6.0%). The most frequently prescribed antibiotics were combination of aminopenicillin with beta lactamase inhibitors (29.4%), metronidazole (28.2%), ceftriaxone (24.4%), azithromycin (15.2%) and cefixime (12.8%). The majority of the patients were discharged from hospital (73.7%) whereas the expired population was 8.6%. Conclusions: This study offers useful information in developing antibiogram for medical wards of Yangon General Hospital, Myanmar. The findings of this study could contribute to improvement in the treatment outcomes.